2017
DOI: 10.1073/pnas.1705451114
|View full text |Cite
|
Sign up to set email alerts
|

Social preferences of future physicians

Abstract: SignificanceThis paper advances scientific understanding of social preference—a topic of longstanding cross-disciplinary interest—by studying the preferences of future physicians. In making treatment decisions, physicians make fundamental tradeoffs between their own (financial) self-interest, patient benefit, and stewardship of social resources. These tradeoffs affect patient health, adoption of new scientific medical technologies, and the equity and efficiency of our health care system. Understanding physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 71 publications
7
40
1
1
Order By: Relevance
“…In accordance with this, some studies highlighted some significant differences in working opportunities ( Hernández-Gálvez and Roldán-Valadez, 2019 ) and in the election of specialty ( Gutiérrez-Cirlos et al, 2017 ) in medical students associated with the medical school, private or public, where they studied their career. In a recent study, Li and colleagues reported that medical students from the best-ranked American universities tend to develop less altruistic and humanitarian professional attitudes ( Li et al, 2017 ). In accordance with this, the lower development of empathy, teamwork, and lifelong learning abilities among students enrolled in the private medical school of Cusco can be another consequence of the exposition to a more elitist professional environment in the absence of a targeted educational program on these three abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this, some studies highlighted some significant differences in working opportunities ( Hernández-Gálvez and Roldán-Valadez, 2019 ) and in the election of specialty ( Gutiérrez-Cirlos et al, 2017 ) in medical students associated with the medical school, private or public, where they studied their career. In a recent study, Li and colleagues reported that medical students from the best-ranked American universities tend to develop less altruistic and humanitarian professional attitudes ( Li et al, 2017 ). In accordance with this, the lower development of empathy, teamwork, and lifelong learning abilities among students enrolled in the private medical school of Cusco can be another consequence of the exposition to a more elitist professional environment in the absence of a targeted educational program on these three abilities.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the development of tools to measure the seriousness of deviations from rational behavior, such as Afriat's (1972) "cost efficiency index" and the "violation index" developed by ?. While such efforts in support of revealed preference theory have been questioned for decades (March, 1978), such tools are applied also in recent RP studies (Li et al, 2017;Li, 2018).…”
Section: Bounded Rationality-and Revealed Preference Studiesmentioning
confidence: 99%
“…One approach is to categorize a given choice sequence as either rational or irrational, and thereafter classify the severity of irrational choices. Examples of this approach can be found in Andreoni and Miller (2002), Fisman et al (2007), Li et al (2017) and (Li, 2018).…”
Section: Bounded Rationality-and Revealed Preference Studiesmentioning
confidence: 99%
“…Note that using the same order for all subjects may lead to an order effect. However, based on findings in health economics experiments, we expected to observe variation in physicians' allocation behavior (Brosig-Koch et al, 2017;Godager & Wiesen, 2013;Li, Dow, & Kariv, 2017) and wanted to avoid additional differences through heterogeneous order effects. Moreover, experimental studies report mixed evidence with a tendency toward the absence of order effects in health contexts (see Brosig-Koch et al, 2019;Buckley et al, 2015Buckley et al, , 2016but Wang, Iversen, Hennig-Schmidt, & Godager, 2017).…”
Section: Methodsmentioning
confidence: 99%